Pertumbuhan dan Hasil Ubi Jalar (Ipomoea Batatas L.) pada Perlakuan Jarak Tanam dan Frekuensi Pemberian Pupuk Hayati - Hapsoh; Isna Rahma Dini; Alif Hadi Ariansyah (Jurnal Galung Tropika, 2026)
Sweet potatoes (Ipomoea batatas L.) are an important source of carbohydrates in Indonesia’s food diversification program. Sweet potato production declined from 2020 to 2021, in line with a decrease in harvested area. One effort to increase the productivity of this crop is through optimal planting distance and the use of biofertilizers containing bacteria that play a role in decomposing organic matter and providing nutrients for the plants. This study aims to determine the effect of the combination of planting distance and biofertilizer application frequency on the growth and yield of sweet potato plants. The study was conducted experimentally using a Completely Randomized Design (CRD) with six treatment combinations of planting distances (75 x 20 cm, 25 cm, and 30 cm) and biofertilizer application frequencies (3 and 4 times), each at 10 ml, with three replications. Analysis results showed that a planting distance of 75 x 30 cm with 3 or 4 applications of biofertilizer optimally increased the number of branches, fresh canopy weight, number and diameter of tubers, and the sweet potato harvest index.